Characterisation of executive deficits in attention-deficit / hyperactivity disorder and avenues for their remediation - O'Connell, Redmond G. (Trinity College (Dublin, Ireland). School of Psychology, 2007)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder that affects both children and adults and is associated with a range of behavioural and cognitive difficulties. This thesis aims to advance our understanding of this disorder by exploring two main themes. The first is that the neural abnormalities underlying executive dysfunction in ADHD can be elucidated by combining electrophysiological measures of brain function with cognitive paradigms for which valid brain-behaviour relationships have been established. The second part of this thesis is concerned with exploring the possibility that our knowledge of the neural instantiation of cognitive functions can provide a new avenue for the development of effective cognitive training strategies for ADHD. Chapter 1 begins by providing a broad overview of ADHD across the lifespan and outlines the theoretical basis for the experiments conducted in this thesis. Chapter 2 discusses the potential value of electrophysiological parameters in ADHD research.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin